Effect of sirolimus on coagulopathy of slow‐flow vascular malformations. Issue 10 (28th June 2019) - Mack, Joana M.; Verkamp, Bethany; Richter, Gresham T.; Nicholas, Richard; Stewart, Kelly; Crary, Shelley E.
Abstract: Background/Objectives: Stagnant blood flow present in slow‐flow vascular malformations can lead to localized intravascular coagulopathy (LIC), measured by elevated D‐dimer levels, low fibrinogen, and/or thrombocytopenia. LIC can lead to localized thrombosis and/or bleeding, resulting in pain, swelling, and functional limitations. Patients with complex vascular malformations treated with sirolimus show clinical improvement in these symptoms. We hypothesized that the clinical benefits of sirolimus may correlate with improvements in coexisting LIC. Design/Methods: A retrospective chart review was performed, including D‐dimer, fibrinogen, and platelet count, in patients with slow‐flow vascular malformations treated with sirolimus. Laboratory values were assessed at three time points (presirolimus, 1‐3 months postsirolimus, and last clinic visit). Clinical response, as defined by decreased pain and swelling, was extracted from the record. Results: Thirty‐five patients at our vascular anomalies center had been prescribed sirolimus between 2014 and 2017. Fifteen patients (12 combined slow‐flow vascular malformations and three pure venous malformations) remained after excluding patients that did not have adequate records or a venous component to their vascular malformation. Patients who did not adhere to the treatment were also excluded. All 15 had elevated D‐dimer levels prior to treatment and there was a statistically significant decrease in D‐dimer levels following treatment with sirolimus. Symptomatic improvement of pain and swelling was reported after 3 months of starting sirolimus in 13/15 patients. Conclusion: This study suggests that sirolimus improves coagulopathy in slow‐flow vascular malformations, as evidenced by reduced D‐dimer levels. Improvement in LIC symptoms also correlates with sirolimus‐corrected coagulopathy.